Analysis of mode choice behavior of students of exclusive schools in Metro Manila the case of Ateneo de Manila University and Miriam College - De Guzman, Mark P. (1999)
Trip purpose consequently is one major factor in the worsening traffic problem in Metro Manila. School trips are one of these trip purposes that contribute to it. Many practical transport policy issues that can alleviate traffic congestion are concerned with mode choice. Travel patterns, trip characteristics, socio-economic characteristics, and transport related policies affect mode choice behavior. The mode choice for this study is generally between car and others (public transport) wherein, public transport includes jeepney, tricycle, bus, taxi, FX (HOV), and LRT. Walk is hereby considered as an access mode. Data collection was conducted on July 14, 15, 16, 19 and August 9 of 1999 at Miriam College and Ateneo de Manila University. Target samples were 400 per university. A total of 350 and 170 samples were collected in Miriam College and Ateneo de Manila respectively.